LEARNING MANAGEMENT TOWARD CHILD-FRIENDLY MADRASAH IBTIDAIYAH IN JEMBER REGENCY - Mukni’ah Mukni’ah; Devi Damayanti; Maghfirotul Firmaning Lestari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Learning management plays a crucial role in creating a child-friendly madrasa environment that supports a safe, comfortable, and conducive learning process for student growth and development. This research focuses on the efforts of State Elementary Madrasahs in Jember Regency to design, implement, and evaluate learning management to realize a child-friendly concept in elementary education. The main objective of this research is to describe the design, implementation, and evaluation of learning management to realize a child-friendly concept in elementary education. This study employed a qualitative approach with a case study method. Data were collected through in-depth interviews with teachers and the head of the madrasah, participant observations in classroom activities, and document analysis related to the learning programs conducted at the school. The collected data were analyzed descriptively to understand the patterns of learning management applied. The findings reveal that, in the planning stage, the madrasah had designed learning programs integrating elements of safety, comfort, and child development needs. During implementation, teachers applied participatory methods, utilized varied learning media, and fostered humanistic interactions with students. The evaluation was carried out through joint reflections among teachers, students, and parents, although challenges such as limited facilities, heavy teacher workload, and the lack of specific training on child-friendly education were still present. In conclusion, learning management towards a child-friendly madrasah requires strong collaboration among the head of the madrasah, teachers, parents, and the community. This study recommends strengthening planning, improving the quality of implementation, and enhancing the evaluation system consistently and sustainably.